Pravda, efikasnost i pravo / Justice, Efficiency and Law: Kritika ekonomske analize prava / Criticism of the Economic Analysis of Law - Durmišević, Tarik (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
In this paper, the author provides a brief analysis, criticism of the economic analysis of law - a theory that has become dominant in the past decades and caused a great deal of controversy and criticism. What is the economic analysis of rights? What is its purpose and what results it delivers? The author traces back its sources, the milieu in which it has thrived and wants to show what neoliberalism truly is and what are its results, as he considers the neoliberalism and economic analysis to be two sides of the same medal. A critique of the economic analysis of law makes one wondering what should be the law‟s real purpose and what should it stand for. Therefore, the author wishes to express the view of justice as a dominant and primal principle of law. Confined by space, time and topic, authors tries not to roam over into depth of the philosophy of law. Considering the topic, general methods of social sciences (analytical, synthetic, inductive and deductive methods) as well as special methods of legal science (theoretical, legal, normative, comparative and historical methods) have been used in making of this paper. The aim is to show that economic analysis of law is a perversion of the law, so to say, its betrayal, due to the abandonment of the idea, or the ideal of justice respectively. The significance of this paper is in the fact that this theory, both its versions - economic analysis of the law as legalistic and its economic one – neoliberalism, is still globally dominant. The paper wants to draw attention to the problems that this theory creates, and this very fact serves the purpose for its publication.